Rancang Bangun Sistem Pelaporan Keuangan Berbasis Web Pada SMK Kesehatan Bali Khresna Medika - Erich Galang Prasetyawan Putra; Ni Made Estiyanti; Eddy Muntina Dharma (Primakara University, 2022)
Bali Khresna Medika Health Vocational School is an institution that is engaged in education at the SMA/K level. The Bali Khresna Medika Health Vocational School is a private school established by individuals through a school committee. Currently, the Bali Khresna Medika Health Vocational School does not yet have a good financial reporting system. This information system is used to exchange information about the school's financial reports every month, especially useful for the finance department (treasurer) to make and determine monthly financial reports. The information system built aims to make it easier to submit monthly school financial reports and save time in making because this reporting system only does data input. The information system implemented will be built using Financial Reporting using In this research report, the researcher uses the Software Development Life Cycle (SDLC) method with the Waterfall development model, using the Mysql Database. While the programming used by the author is PHP (Hypertext Preprocessor) and the end result is a web application that connects to a database that is run on one (single) server. The purpose of this study is to provide convenience in the process of inputting payment and expenditure data, to help speed up the performance of the finance department, to increase accuracy in conducting financial transactions. All transactions will be saved automatically to financial reports which include budgets, cash inflows, cash outflows, general journals, ledgers, income statements, and balance sheets, BOS funds and school inventory data. Suggestions that later this system can be developed by adding or modifying the payroll system feature which will later be able to help the principal and the head of the foundation to see the payroll procedures in this school's financial reporting system.